Características de deglutição e nutricionais de indivíduos póscovid-19 - Arteaga, Erica Andrea Vega (2023)
Objective: To characterize swallowing using instruments for clinical and objective assessment and screening for oropharyngeal dysphagia, to verify the prevalence of oropharyngeal dysphagia and to relate the variables nutritional status, life expectancy scores and length of stay, by sex. Methods: Cross-sectional, observational study carried out at the post-COVID-19 outpatient clinic of a University Hospital in the central region of RS, from August/2021 to July/2022. 50 individuals were evaluated after hospitalization due to COVID-19. Of these, 23 were women and 27 men. Individuals under 18 years old, with laryngeal disorders, with neurological, psychiatric or gastric impairments prior to COVID-19, and with tracheostomy were excluded. All eligible subjects were submitted to the following evaluations: Mini Mental State Examination, Eating Assessment Tool -10, Speech Therapy Protocol for Dysphagia Risk Assessment, Volume–Viscosity Swallowing Test, Swallowing Videoendoscopy, nutritional assessment by bioelectrical impedance, handgrip strength, body mass index and Mini Nutritional Assessment. The age-adjusted life estimate was calculated using the Charlson Comorbidity Index instrument corrected for age. Additional data were collected, such as comorbidities, gender, need for ventilatory support, length of hospital stay and the time interval between hospital discharge and the first swallowing assessment. Results: The mean evaluation time after hospital discharge was, in most cases, over six months. The overall mean age was 54.28 years, and men were slightly older (57.96 years) when compared to women (49.95 years). When analyzing the risk for dysphagia, by sex, it can be seen that women had a 47.80% risk according to the Eating Assessment Tool -10; 73.90% by the Volume–Viscosity Swallowing Test; in Swallowing Videoendoscopy, 56.50% had functional swallowing and 34.80% had dysphagia, and according to the Speech-Language Pathology Risk Assessment Protocol for Dysphagia, 60.9% had functional swallowing. While in men, the risk for dysphagia in the Eating Assessment Tool -10 was 7.40%, 77.80% in the Volume–Viscosity Swallowing Test, 33.30% had dysphagia in the Swallowing Videoendoscopy and 3.7% had mild dysphagia by the Speech-Language Pathology Risk Assessment Protocol for Dysphagia. Women (33.09±5.98) had a slightly higher obesity rate than men (31.49±4.62), a lower median weight loss during hospitalization was observed in women 6 (0 – 30) compared with 12 men (0 – 45), and both sexes were at risk of malnutrition. The risk of sarcopenia was observed in 48% of the sample. As for the estimated life by the Charlson Comorbidity Index corrected for age, an average of 77.36% was observed. Conclusion: The population studied showed a relatively significant prevalence of swallowing disorders, verified through clinical and, mainly, objective evaluation, with no difference by sex, except in the screening protocol (Eating Assessment Tool -10), in which the female population perceived and expressed their swallowing disorders in greater proportion in relation to men. The study participants belonged to the first and second wave of the disease, where the average evaluation time after hospital discharge was in most cases greater than six months.